National, Transnational and European Legal Histories: Problems and Paradigms. A Scottish perspective - John W. Cairns (Clio@Themis)
This article explores the different ways of writing legal history, using concrete examples to demonstrate the advantages and disadvantages of each. The possibilities of national, European and transnational legal histories are discussed, with a conclusion that most good legal history has always had a comparative or transnational aspect.